Testicular hypofunction and multiple sclerosis risk: a record-linkage study. - Pakpoor, J; Goldacre, R; Schmierer, K; Giovannoni, G; Goldacre, M (2014)
The influence of gonadal hormones on multiple sclerosis (MS) is not well characterized and has thus far been investigated primarily in animal models or as a proposed therapeutic approach. We investigated a potential association between testicular hypofunction, as a proxy for low testosterone levels, and MS risk through analysis of linked English national Hospital Episode Statistics from 1999 to 2011. We report a strong positive association between testicular hypofunction and subsequent MS (rate ratio = 4.62, 95% confidence interval = 2.3-8.24, p < 0.0001). Future work should aim more directly to elucidate the relationship between testosterone levels and MS in both males and females.